Can the Principles of Franchising be used to Improve Water Supply and Sanitation Services? A Preliminary Analysis - van Ginneken, Meike (World Bank, Washington, DC, 2014)
Improving water supply and sanitation (WSS) services is a key mechanism for reducing poverty. WSS services contribute directly or indirectly to income generation, health, and education. Water is an intrinsic element of the Millennium Development Goals agreed upon by the international community in 2000. Halving by 2015, the proportion of people without sustainable access to safe drinking water and basic sanitation is one of the time bound targets that are embodied in the Millennium Development Goals. Reaching this target requires that roughly one quarter of a million people per day gain access to safe water and one third of a million per day gain access to adequate sanitation. Currently, in developing countries, the overall effectiveness of WSS service provision is disappointing due to such factors as: poor management, inadequate investment, and political interference. Substantially increasing the number of people with sustainable access to WSS requires a transformation of long-established sector approaches as well as a substantial increase in WSS investments in the developing world. Foremost among reform measures are the introduction of sound policies and effective institutions at all levels. Strengthened institutions will be better able to generate cash flows, close revenue gaps, and attract financial resources. New avenues for public-public and public-private partnerships are needed. Building technical, managerial and operational capacity is, therefore, an important component of efforts to improve and expand service delivery in the WSS sector.